The political positioning strategy of the National Democratic (NasDem) Party in the Prabowo Subianto - Gibran Rakabuming Raka government - Subekti, Dimas (Privietlab, 2025)
This article aims to analyze the political positioning strategy of the NasDem Party in the context of the Prabowo Subianto – Gibran Rakabuming Raka administration after the 2024 elections. This study employs a qualitative method, with a literature review as the primary data collection technique. The findings reveal that NasDem implements three main strategies: market-oriented (aligning the party's stance with public perception), differentiation (creating strategic distance from coalition parties to establish an independent image), and functional positioning (optimizing its role in parliament as a tangible contribution). These strategies have enabled NasDem to build an image as a rational, ethical, and non-opportunistic party while maintaining long-term political flexibility. These findings contribute to studies on Indonesian political parties, particularly in understanding the dynamics of party positions outside executive power and the importance of positioning in maintaining electoral support sustainability within a complex multiparty system.